Peformance negra: desmontagem de uma poética autoral - Rodrigo Augusto de Souza Antero (2022)
Study in the Performing Arts research line, in which I elaborated a disassembly (DIÉGUEZ, 2018) of the authorial creative process entitled Projeto Córpe, composed of a trilogy of performances: Projeto Servir, Ex-Tintos and ex-tinto. These autobiographical works investigate possibilities of relationships with the materiality of white and transparent disposable plastic cups for the composition of performative narratives, in which the public can participate in a creative and interactive way. Animating these objects, I discovered forms of masking in which, by dancing the masks (PAULINO, 2010), I stripped my blackness from the processes of whitening and racism experienced between art and life. In this trilogy, I reflect about the disposability both in the sense of environmental protection and in the context of human relations. I question how the notion of disposability can produce the extinction of something or someone, someone being any living being, especially with regard to my existence: a black and homosexual person in the world. I use a writing methodology called escrevivências (EVARISTO, 2008) inspired by the black author Conceição Evaristo, in an artist-researcher’s diary, in which I sought to study and interpret my own black poetics (MACHADO, 2015), a phenomenon researched in this dissertation. The references Abdias Nascimento, Frantz Fanon, Grada Kilomba, Leda Maria Martins, Marcos Antônio Alexandre and Maria Beatriz Nascimento are the parameters to discuss and interweave the aspects concerning black performativity in the works that compose the Projeto Córpe. This autobiographical research intends to contribute to studies in black poetics, narratives from this place of enunciation in search of an ethical, aesthetic and political discourse.